A deep insight on the coal ash-to-slag transformation behavior during the entrained flow gasification process. (1st April 2021) - Shen, Zhongjie; Nikolic, Heather; Caudill, Landon S.; Liu, Kunlei
Highlights: Shortened temperature zone in entrained flow gasifier causes slag transformation. Transition from anorthite to diopside related to temperature and residual carbon. A dimensionless number was defined to characterize degree of slag polymerization. A general mechanism is built to optimize slag flow in multiple coal utilization. Abstract: Recent research provided deep insight on the coal ash-to-slag transformation characterization during the entrained flow gasification process, with experimentation on a 40 kg/hr (dry basis) coal-fed opposed multi-burner (OMB) entrained flow gasifier and simulation via FactSage™ software. A general mechanism is presented to relate the gasifier design temperature, ash fluid temperature, and operating temperature with the degree of the slag polymerization. The change of the high temperature zone, the corresponding particle residence time in the high temperature zone, and syngas composition have obvious effects on the slag mineral transformation behavior. Mineral types formed on the wall of the gasifier chamber were mainly anorthite (CaAl2 Si2 O8 ), aluminum oxide (Al2 O3 ), and calcium sulfide (CaS). These minerals transformed to anorthite and diopside (CaMgSi2 O6 ) at the slag hole zone, while the minerals at the lock hopper were anorthite, orthoclase (KAlSi3 O8 ), quartz (SiO2 ), gypsum (CaSO4 ), calcite (CaCO3 ), and halite (NaCl). FactSage™ predicted minerals as anorthite, diopside, orthoclase, and albite (NaAlSi3 O8 ), etc., where the slag temperature was below the ash fluid temperature and when the ratios of CO/CO2 and (CO + H2 )/CO2 were lower than 1.0 and 2.0, respectively. By simulation, residual carbon was found to be the dominant factor over syngas composition to cause mineral transformation, and this was verified experimentally. The Ca-based crystals, typically anorthite, was shifted to diopside, near the slag hole zone, and a linear relationship was found between the content ratios of diopside/(anorthite + diopside), CaO/SiO2, and (CaO + MgO)/SiO2 . A dimensionless number, θ, was defined to characterize the changing chemical composition and the degree of slag polymerization, with temperature deviation from the design condition. Three zones of θ were identified and related to the deviation between the actual gasification condition from the design condition. A low slag polymerization degree corresponded with a higher temperature deviation between the actual condition and design condition, and this proved that increased residual carbon content and changing iron valence state increased the mineral types when the slag temperature was below the ash fluid temperature.